Nanostructured Materials: A Review on its Application in Water Treatment - Ifijen, Ikhazuagbe H.; Ikhuoria, Esther U.; Maliki, Muniratu; Otabor, Godfrey O.; Aigbodion, Areguamen I. (TMS 2022 151st Annual Meeting & Exhibition Supplemental Proceedings, 2022)
Nano-sized materials have been the subject of active research and advancement worldwide in recent years due to the extraordinary properties resulting from nano-size, such as enhanced catalysis and adsorptionAdsorption properties and high reactivity. Diverse investigations have revealed that nanomaterials can efficiently eliminate several pollutantsPollutant in water and thus have been favourably applied in water and wastewaterWastewater treatment. This review focused on some broadly investigated nanomaterials, carbon nanotubes, graphene-based nanomaterials, metal oxide-based nano-adsorbents, and bimetal oxide magnetic nanomaterials. The numerous studies carried out on the adsorptive capability of nanostructured materials show that they are very promising for water treatment.